Doses from Rn-222, Ra-226, and Ra-228 in groundwater from Guarani aquifer, South America - Bonotto, Daniel Marcos [UNESP] (Elsevier B.V., 2004)
Groundwater samples were analysed for Rn-222, Ra-226, and Ra-228 in Guarani aquifer spreading around I million kin 2 within four countries in South America, and it was found that their activity concentrations are lognormally distributed. Population-weighted average activity concentration for these radionuclides allowed to estimate a value: either slightly higher (0.13 mSv/year) than 0.1 mSv for the total effective dose or two times higher (0.21 mSv/year) than this limit, depending on the choice of the dose conversion factor. Such calculation adds useful information for the appropriate management of this transboundary aquifer that is socially and economically very important to about 15 million inhabitants living in Brazil, Argentina, Uruguay and Paraguay. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: radionuclides; groundwater; Guarani aquifer; doses; health risk